Enhanced stability and optoelectronic properties of MAPbI3 films by a cationic surface-active agent for perovskite solar cells. Issue 23 (25th May 2018) - Zhao, He; Wang, Shirong; Sun, Mengna; Zhang, Fei; Li, Xianggao; Xiao, Yin
Abstract : Passivation and hydrophobic effects can significantly enhance the stability and optoelectronic properties of MAPbI3 films. Abstract : The insufficient stability of perovskite solar cells (PSCs) has considerably restrained their development and applications. Herein, we demonstrate an approach to prepare PSCs with high stability and efficiency by adding n -octyltrimethylammonium bromide (OTAB) to the precursor solution. In the resultant films, the charge trap density exhibits a significant reduction, and the long-term stability shows a remarkable enhancement. Upon adding 0.5 mg mL −1 OTAB, the power conversion efficiency (PCE) of PSCs reaches 18.32% under simulated AM 1.5G solar illumination, which represents an increase of 16% compared to the pristine devices. Moreover, the OTAB-modified devices demonstrate excellent performances both in high-temperature (70 °C, 40 ± 5% relative humidity) and high-humidity (25 °C, 75 ± 5% relative humidity) environments. These results indicate a very promising approach to improve the comprehensive performance of PSCs.